Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.